Correlation between Family Support and Obedience of Blood Pressure Control in Patients with Primary Hypertension - Ni Kadek Yuni Lestari Yuni (KHD Production, 2023)
Hypertension is a major health problem for non-communicable diseases. Family support is the best preventive strategy to help family members maintain their health. This study aimed to determine the correlation between family support and obedience to blood pressure control in patients with primary hypertension. This research method is a quantitative descriptive correlation design with a cross-sectional approach. The sample was 71 patients with primary hypertension using the purposive sampling technique. The results showed that most patients with primary hypertension were in the good category about 47 respondents (66.20%) and compliance with blood pressure control in patients with primary hypertension was in the high category about 41 respondents (57.75%). The analysis using the rank Spearman test showed that the value of p = 0.000 (p<0,05) indicates a correlation between family support and compliance with blood pressure control. r value is 0,570 (moderate strength) and positive correlation direction means that the better the family support, the higher blood pressure control compliance. Family support has a significant influence on family members who suffer from hypertension, the family functions to carry out nursing care practices to care for sick family members, including obediently controlling blood pressure. Based on the research results, it is hoped that the Community Health Center can provide ongoing education about managing hypertensive patients, especially family involvement in patient care.